2020
DOI: 10.1111/head.14042
|View full text |Cite
|
Sign up to set email alerts
|

Remote electrical neuromodulation for acute treatment of migraine in adolescents

Abstract: Objectives: Migraine is a common disabling neurological disorder. Current acute treatments for migraine in adolescents are mostly pharmacological and may have limited effectiveness, can cause side effects, and may lead to medication overuse. There is an unmet need for effective and well-tolerated treatments. Remote electrical neuromodulation (REN) is a novel acute treatment of migraine that stimulates upper arm peripheral nerves to induce conditioned pain modulation (CPM)-an endogenous analgesic mechanism. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 27 publications
4
49
0
Order By: Relevance
“…Twelve participants (13.2%) reported mild short-term side effects, most of which were expected and have been observed in previous studies [17,23]. These results provide further support for the favorable tolerability and safety profile of REN found in clinical trials in episodic and chronic migraine in adults [16][17][18][19][20][21]23], and adolescents [24].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Twelve participants (13.2%) reported mild short-term side effects, most of which were expected and have been observed in previous studies [17,23]. These results provide further support for the favorable tolerability and safety profile of REN found in clinical trials in episodic and chronic migraine in adults [16][17][18][19][20][21]23], and adolescents [24].…”
Section: Discussionsupporting
confidence: 84%
“…1). Efficacy studies have demonstrated that REN is safe and clinically beneficial for the acute treatment of migraine in adults with episodic migraine [16][17][18][19][20][21][22], adults with chronic migraine [23], and adolescents with migraine [24]. A comparison of the efficacy of REN to that of acute migraine medications indicated that REN has non-inferior efficacy compared to the tested acute migraine therapies [20].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy in adults has induced an open trial in children which was recently finished and suggested an efficacy also in children and adolescents [ 58 ].…”
Section: Neurostimulation Methodsmentioning
confidence: 99%
“…The REN device achieves therapeutic effects by delivering transcutaneous electrical stimulation to the upper arm, which induces conditioned pain modulation and activates a descending endogenous analgesia 73 . It was FDA‐cleared for the acute treatment of migraine in adults based on positive results in a randomized controlled clinical trial 45 ; it was cleared for the acute treatment of migraine and chronic migraine in patients aged 12 years and older based on data from an open‐label, single‐arm, multicenter study 74 . As with many nondrug therapeutic options, REN has shown good tolerability and safety in clinical trials; paresthesia in the area of the device was the most common side effect 45,46 …”
Section: Acute Treatmentmentioning
confidence: 99%